Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $x=5$, $y=7$, $z=6$

$x+y = 2z$

Rearranging, $x-2z = -y$

and $x = -y+2z$

Multiply both sides respectively. $x^2-2xz = y^2-2yz$

$$x^2-2xz+z^2 = y^2-2yz+z^2$$ $$(x-z)^2 = (y-z)^2$$ $$x-z = y-z$$ Hence $x=y$, or $5 = 7$

Well, the conclusion is clearly false, but what went wrong? I think it may be the step in which one square roots both sides because it's taking out one solution?

share|improve this question
1  
Maybe when you took a squre root: $x^2=y^2$ implies $x=y$ or $x=-y$. indeed $x-z=z-y=-1$ –  Belgi Apr 28 '12 at 0:42

4 Answers 4

up vote 17 down vote accepted

Hint $\ $ When debugging proofs on abstract objects, the problem may become simpler to spot after specializing to more concrete objects. The symbols $\rm\:x,y,z\:$ denote abstract numbers, so let's specialize them to their concrete number values: $\rm\:x = 5,\: y=7,\: z = 6,\:$ yielding this "proof" $$\begin{eqnarray} 5 + 7 &=&\: 2\cdot 6 \\ 5- 2\cdot 6 &=&\: -7 \\ \cdots\ &=&\ \cdots \\ (5-6)^2\! &=&\: (7-6)^2 \\ 5-6\ \ \:&=&\:\ \ 7-6\: \end{eqnarray}$$ Now you can determine which inference is incorrect by determining the first false equation above. If equation number $\rm\: n\!+\!1\:$ is false then the inference from equation $\rm\:n\:$ to $\rm\:n\!+\!1\:$ is incorrect. You'll find that the final inference is false, the last equation being false. Now the error is clear.

Analogous methods prove helpful generally: when studying abstract objects and something is not clear, look at concrete specializations to gain further insight on the general case.

share|improve this answer
    
I like this answer best so far, since it gives a more general method than just looking at this particular problem. –  Doug Spoonwood Apr 28 '12 at 2:06

You have $x=−y+2z$ and $x−2z=−y$ then you multiply both sides. I think you are computing $-xy$ in two ways: for the first $-xy=y^2-2zy$ for the second $-xy=-2zx+x^2$ so you have $y^2-2zy=x^2-2zx$. Adding $z^2$ to both sides gives $(y-z)^2=(x-z)^2$. But now taking square roots gives $|y-z|=|x-z|$.

If you try to remove the absolute value signs then you get $y-z=x-z$ if both are positive or negative but $y-z=-(x-z)$ if these have opposite signs. In the first case this leads to $y=x$, and in the second case $y=-x+2z$. For your example, the second case applies $7=-5+2\cdot6$.

share|improve this answer

If $(x-z)^2 = (y-z)^2$ then $x-y = \pm(y-z)$.

share|improve this answer
    
That is essential what I said. –  Pedro Tamaroff Apr 28 '12 at 0:46
    
And what you said is essentially what I said. –  Michael Hardy Apr 28 '12 at 0:48
1  
Touchè. I'm just saying there is no need for a duplicate. –  Pedro Tamaroff Apr 28 '12 at 0:49
6  
So, shall we fight a duel to decide which one should be deleted? –  Michael Hardy Apr 28 '12 at 2:32

What you have is

$$(x-z)^2=(y-z)^2$$

Note that $y-z$ is positive, but $x-z$ is negative. Thus you have to consider the absolut value when taking the square root.

This means

$$|x-z| = y-z$$

But not

$$x-z = y-z$$

share|improve this answer
    
A few seconds before saving my own answer, I go the usual notice that someone else had answered, and that was this answer. My version is essentially the same thing, but maybe more simply expressed. Here's a confession: I believe in simplicity. –  Michael Hardy Apr 28 '12 at 2:31
    
....and Bill Dubuque's got a point too. –  Michael Hardy Apr 28 '12 at 2:32

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.